Missing the boat: Indonesian Kompas newspaper’s 1995 reporting on asylum seekers from East Timor - Hearman, Vannessa (Swinburne University, 2018)
The Indonesian government reported that a group of people had stolen the Tasi Diak (Good Sea) 119, a wooden fishing boat, from the port of Hera in May 1995. Five days after the boat was reported missing, it arrived in Darwin, Australia, carrying seventeen Timorese: 15 young men, 2 women and a baby. This was to be the only boat arrival of asylum seekers from Indonesian-occupied East Timor in the 1990s. The boat passengers claimed asylum on the grounds of Indonesian persecution but were sent to detention at the Curtin Air Force Base in Western Australia for approximately 7 weeks in June-July 1995. This paper analyses the coverage, between June and August 1995, of East Timor generally and the boat voyage specifically in the Indonesian national newspaper, Kompas compared to the coverage in Australian newspapers. The paper shows the constraints experienced by a media operating under the authoritarian New Order regime in a time of media bans and the jailing of writers and activists.